2004
DOI: 10.1021/mp049952s
|View full text |Cite
|
Sign up to set email alerts
|

Circumventing P-Glycoprotein-Mediated Cellular Efflux of Quinidine by Prodrug Derivatization

Abstract: The objective of this study is to investigate whether transporter-targeted prodrug derivatization of quinidine, a model P-glycoprotein (P-gp) substrate, can circumvent P-gp-mediated efflux. The L-valine ester of quinidine (val-quinidine) was synthesized in our laboratory. Uptake and transport studies were carried out using the MDCKII-MDRI cell line at 37 degrees C for 10 min and 3 h, respectively. [3H]Ritonavir and cyclosporine were also used as model P-gp substrates to delineate the kinetics of translocation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2
1

Relationship

5
5

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 35 publications
1
23
0
Order By: Relevance
“…This result indicated that DP is highly susceptible to alkaline hydrolysis relative to acidic hydrolysis. Similar results have been observed for a wide range of amino acid prodrugs developed previously in our laboratory (35,36,39,40). Lower degradation half-life at pH 7.4 suggests that a large amount of DP may degrade in precorneal tear fluid upon topical administration to regenerate prednisolone.…”
Section: Buffer Stability Studiessupporting
confidence: 86%
“…This result indicated that DP is highly susceptible to alkaline hydrolysis relative to acidic hydrolysis. Similar results have been observed for a wide range of amino acid prodrugs developed previously in our laboratory (35,36,39,40). Lower degradation half-life at pH 7.4 suggests that a large amount of DP may degrade in precorneal tear fluid upon topical administration to regenerate prednisolone.…”
Section: Buffer Stability Studiessupporting
confidence: 86%
“…In a drug discovery process, prodrugs are often designed to improve the pharmacological and pharmacokinetic properties of the drugs. Val-quinidine, a prodrug obtained by derivatization of quinidine was reported successful in circumventing P-gp transport (Jain et al, 2004). The first and third generation PAMAM dendrimer based prodrugs showed potency as membrane permeability enhancing P-gp inhibitors for P-gp substrate drugs (Thiagarajan et al, 2010).…”
Section: Pharmaceutical Prodrugsmentioning
confidence: 99%
“…We have recently reported from our laboratory that peptide prodrug modification of compounds that are P-gp substrates resulted in partial evasion of P-gp mediated efflux (Jain et al, 2004;Jain et al, 2005). Following this discovery, we have used MDCKII-MDR1 cell line for studying peptide-mediated drug influx of peptide prodrug derivatives of compounds which were originally P-gp substrates.…”
Section: Introductionmentioning
confidence: 99%